Kajian Hukum Kebijakan Energi Terbarukan Indonesia dan Realisasinya Menuju Tahun 2025 - Purba, Erik Timoteus; Wulandari, Christine; Bakri, Samsul (Universitas Sang Bumi Ruwa Jurai, 2024)
Indonesia is committed to switching to renewable energy in the face of the global energy crisis and climate change. This paper examines the evolution of renewable energy policies in Indonesia, analyzes changes in energy mix targets, and evaluates achievements and challenges in its realization towards 2025. This research uses a qualitative approach by collecting data from laws and regulations, government reports, scientific journals, and related sources. The results of the study show that renewable energy policies in Indonesia have undergone significant development, but there are still a number of challenges in achieving the 23% energy mix target by 2025. This paper provides policy recommendations to address these challenges and accelerate the energy transition towards a sustainable future